Analyses of morphological and molecular characteristics of Telotylenchinae from Iran point at the validity of the genera Bitylenchus and Sauertylenchus - Azizi, Kourosh; Eskandari, Ali; Karegar, Akbar; Ghaderi, Reza; Elsen, Sven Van Den; Holterman, Martijn; Helder, Johannes (Zootaxa, 2022)
To investigate relationships within the subfamily Telotylenchinae, more than 500 soil samples were collected from various natural and agricultural habitats in several localities of Iran. Individuals of seven known species, including Bitylenchus dubius, B. parvus, B. serranus, Sauertylenchus maximus, Tylenchorhynchus clarus, T. microconus and Trophurus ussuriensis, were recovered and characterized based on morphological and morphometric characters. Furthermore, phylogenetic relationships within representatives of the subfamily Telotylenchinae were explored using 13 sequences from the D2-D3 expansion regions of 28S ribosomal (r) DNA and 13 sequences for the partial 18S rDNA genes obtained in the present study. Analyses based on the relatively conserved 18S rDNA gene underlined the polyphyletic status of Tylenchorhynchus sensu lato, as three clusters representing Tylenchorhynchus, Bitylenchus and Sauertylenchus were well separated, and interspersed by, e.g., representatives of the Macrotrophurinae. Analysis of the more variable D2-D3 28S rDNA sequences suggested at least four clades within the subfamily Telotylenchinae: two clades dominated by Tylenchorhynchus species; a third clade harbouring representatives of Sauertylenchus, Bitylenchus, and Paratrophurus in distinct but unresolved branches;and a fourth clade dominated by Trophurus species. Although no molecular information was available from a number of genera that were originally gathered under Tylenchorhynchus sensu lato, we concluded that both Bitylenchus and Sauertylenchus should be seen as valid Telotylenchinae genera related to, but distinct from Tylenchorhynchus.